ANALISIS PENGARUH BAURAN PEMASARAN STATUS SOSIAL EKONOMI DAN MOTIVASI TERHADAP KEPUTUSAN MAHASISWA DALAM MEMILIH KULIAH (Studi Pada Lembaga Pendidikan dan Pengembangan Profesi Indonesia (LP3I) Business College – Cabang Banjarmasin) - Sis Rahardjo; Muhammad Riza Firdaus (JWM (JURNAL WAWASAN MANAJEMEN), 2015)
Education is an important factor that played a role in all sectors. Decisions students choose further education after high school, influenced by the marketing mix (program, price, promotion place, process, physical facilities, and people), socio-economic status and motivation. The problem in this research is the extent to which the influence of the marketing mix, socioeconomic status and motivation of the student’s decision to study at the Institute of Education and Professional Development Indonesia (LP3I) Business College - Banjarmasin. The approach in this research is descriptive and quantitative survey supported, are explanatory, where the variable measured with Likert scale. Methods of data collection with a list of questions to 121 respondents in the LP3I–Business College = Banjarmasin. The results showed that there is a positive and significant effect of the marketing mix (product, price, promotion, location, process, people and physical appearance) to motivate students in choosing LP3I Business College Banjarmasin; Marketing mix (product, price, promotion, location, process, people and physical appearance) positive and significant impact on student’s decision in choosing LP3I Business College Banjarmasin; Socio-economic background and significant positive effect on student motivation in choosing LP3I Business College Banjarmasin; Socio-economic background factors positive and significant impact on student’s decision in choosing LP3I Business College Banjarmasin and motivation factor positive and significant impact on student’s decision in choosing LP3I Business College Banjarmasin